2021
DOI: 10.1186/s12940-021-00709-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to bisphenol A and autistic- and ADHD-related symptoms in children aged 2 and5 years from the Odense Child Cohort

Abstract: Background Bisphenol A (BPA) is a non-persistent chemical with endocrine disrupting abilities used in a variety of consumer products. Fetal exposure to BPA is of concern due to the elevated sensitivity, which particularly relates to the developing brain. Several epidemiological studies have investigated the association between prenatal BPA exposure and neurodevelopment, but the results have been inconclusive. Objective To assess the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 66 publications
(115 reference statements)
0
22
0
2
Order By: Relevance
“…Bisphenol A (BPA) is an organic synthetic compound that exerts weak estrogenic activities and is associated with increased ASD risk ( Stein et al, 2015 ; Hansen et al, 2021 ). ASD is diagnosed in males much more frequently than in females, at about a 4:1 ratio, and it has been posited that BPA exposure could play a role in ASD sex differences ( Thongkorn et al, 2019 ).…”
Section: Multigenerational Risk For Asdmentioning
confidence: 99%
“…Bisphenol A (BPA) is an organic synthetic compound that exerts weak estrogenic activities and is associated with increased ASD risk ( Stein et al, 2015 ; Hansen et al, 2021 ). ASD is diagnosed in males much more frequently than in females, at about a 4:1 ratio, and it has been posited that BPA exposure could play a role in ASD sex differences ( Thongkorn et al, 2019 ).…”
Section: Multigenerational Risk For Asdmentioning
confidence: 99%
“…Une dizaine d'études de cohortes publiées depuis 2009 dans différents pays (44-56) ont décrit des associations entre une exposition prénatale (et parfois aussi postnatale) et le neurodéveloppement chez l'enfant à différents âges (Tableau 3). Chez l'enfant d'âge préscolaire (44,46,51,53) les effets associés concernent le plus souvent des altérations du comportement externalisé (hyperactivité, agressivité) ou internalisé (anxiété/dépression), également des problèmes de langage ( 54), des altérations de la mémoire de travail et de la capacité de planification (51), des symptômes TSA (55). Chez les enfants d'âge scolaire, les études indiquent principalement des manifestations du comportement internalisé et externalisé (45,(47)(48)(49)(50) et parfois des déficits cognitifs et des fonctions exécutives (45).…”
Section: Données éPidémiologiquesunclassified
“…Trois études indiquent cependant des associations avec l'exposition prénatale et postnatale (45,46,49). Des études décrivent des associations significatives avec les effets comportementaux uniquement chez les garçons (48,50,53) ou chez les filles (44,55) ou dans les deux sexes (45,51) mais s'exprimant différemment chez la fille et le garçon et différemment selon le moment d'exposition prénatal ou postnatal (45)(46)(47)49). Dans un échantillon d'enfants âgés de 8 à 15 ans issu de l'enquête Nhanes (2003)(2004), les concentrations les plus élevées de BPA urinaire étaient associées avec le TDAH.…”
Section: Données éPidémiologiquesunclassified
“…BPA exposure is associated with human disease and dysfunction, including fertility problems, cancer, obesity, and neurobehavioral abnormalities ( Rochester, 2013 ). In particular, BPA exposure is correlated with the development of neurodevelopmental disorders, such as autism spectrum disorder (ASD), and children diagnosed with ASD have higher BPA metabolites in their urine ( de Cock et al, 2012 ; Stein et al, 2015 ; Yoo et al, 2020 ; Hansen et al, 2021 ). Further, multiple studies have shown that behavioral problems correlate with maternal BPA exposure ( Ejaredar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%